Hedonic property prices and coastal beach width. Issue 3 (28th September 2021) - Landry, Craig E.; Turner, Dylan; Allen, Tom
Abstract: Previous research suggests that coastal housing values capitalize the quality of nearby beaches but note potential problems related to measurement errors and reverse causation due to beach replenishment. We offer the first hedonic analysis of communities not engaged in beach replenishment, obviating concern over reverse causation. Statistical evidence supports hedonic specifications that account for proximity to the shoreline, though marginal willingness to pay (WTP) varies with the specification. Using an instrumental variables approach, we find significant downward bias in ordinary least squares estimates of marginal WTP derived from the sale of vacant lots compared to two‐stage least squares estimates on the same vacant lots. Notably, we do not find evidence of the same downward bias in WTP derived from the sale of existing homes. Abstract : Related Content: Valuing impacts of proximity to Saguaro National Park on house prices